Transformasi Pembelajaran dan Prinsip-Prinsip Metodologi Pendidikan Agama Islam dalam Penguatan Pengalaman Belajar Siswa - Andi Abd. Muis; Muh. Hafiz Ahmad; Anugrah Anugrah; Muh. Yusuf; Kasna Kasna; Muslimin B; Abdul Azan Tuanaya; Fitraya Fitraya; Annisa Ansar; Nurpitra Nurpitra; Isdawati Isdawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning transformation is a strategic demand in modern education, including in the context of Islamic Religious Education (PAI). The shift in the learning paradigm from conventional to more active, participatory, and student-centered learning requires the application of adaptive and contextual methodological principles. This literature review aims to examine how learning transformation and Islamic Religious Education (PAI) methodological principles contribute to strengthening students' learning experiences. This research uses a literature review approach by reviewing various scientific sources from national and international journals for the 2019–2025 period. The results indicate that Islamic Religious Education (PAI) learning transformation emphasizes not only mastery of religious material but also the internalization of spiritual, moral, and social values ​​relevant to students' lives. Methodological principles such as role modeling, habituation, active participation, reflection, and contextualization are fundamental to creating meaningful learning experiences. By utilizing digital technology and a humanistic approach, teachers can foster deeper emotional and spiritual engagement in students. This study confirms that Islamic Religious Education (PAI) learning transformation, grounded in a strong and contextual methodology, can strengthen students' learning experiences holistically, across cognitive, affective, and psychomotor aspects.